Peningkatan Pengembangan SDM Dengan Membangun Karakteristik Berjiwa Wirausaha Dan Budaya Kerja Pada UMKM Mandiri Jaya - Ela Nurlela; Yanti Susanti; Ridha Raya Dinayah; Melianti Melianti (LKP KARYA PRIMA KURSUS, 2025)
This community service program aims to enhance human resource development by fostering entrepreneurial characteristics and work culture within UMKM Mandiri Jaya. The main issue identified was the limited understanding among employees regarding the importance of work culture and entrepreneurial traits in sustaining business continuity. The proposed solution involved educational activities using lectures, interactive discussions, and comprehension assessments through pre-test and post-test instruments. Conducted in Rancailat Village, Kresek District, Tangerang Regency, the program engaged 24 participants. Results showed improved understanding of work culture and entrepreneurship, reflected in higher post-test scores and a statistically significant regression model. An R Square of 0.968 and F value of 315.222 indicate that the variables of HR development and entrepreneurial characteristics jointly explain 96.8% of the variance in work culture. In conclusion, this activity successfully enhanced participants’ knowledge and attitudes toward HR development, and strengthened UMKM competitiveness through the cultivation of a productive work culture and adaptive entrepreneurial mindset.